1984
DOI: 10.1042/bj2240093
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the growth-promoting, lipolytic, diabetogenic and immunological properties of pituitary and recombinant-DNA-derived bovine growth hormone (somatotropin)

Abstract: The physiological mechanisms by which growth hormone (somatotropin) exerts its several metabolic activities remain poorly understood. In particular, there is disagreement as to whether the diabetogenic and lipolytic activities of the hormone are intrinsic properties of the molecule or are the result of contamination with other pituitary components. The availability of recombinant-DNA-derived bovine growth hormone (rebGH) presented an opportunity to compare the biological activities of rebGH and pituitary bGH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1
2

Year Published

1988
1988
2001
2001

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 33 publications
4
33
1
2
Order By: Relevance
“…In that study, milk lactose production represented a major use of lost glucose. McDowell et al (1987b) demonstrated that rbGH treatments reduced glucose uptake by the hindlimb muscle and increased glucose uptake by the mammary gland, lending further support that diabetogenesis is an inherent property ofthe rbGH molecule (Hart et al 1984). We additionally propose that IGF-I plays a fundamental role in the diabetogenic activities of rbGH.…”
Section: Effects Of Growth Hormone On Body Conditionmentioning
confidence: 78%
See 1 more Smart Citation
“…In that study, milk lactose production represented a major use of lost glucose. McDowell et al (1987b) demonstrated that rbGH treatments reduced glucose uptake by the hindlimb muscle and increased glucose uptake by the mammary gland, lending further support that diabetogenesis is an inherent property ofthe rbGH molecule (Hart et al 1984). We additionally propose that IGF-I plays a fundamental role in the diabetogenic activities of rbGH.…”
Section: Effects Of Growth Hormone On Body Conditionmentioning
confidence: 78%
“…By most immunological, receptor-binding, bioassay, and biopotency criteria, pituitary-and recombinant DNA-derived sources of bovine GH were originally shown to be similar or identical (Hart et al 1984;Wingfield et al 1987 Wingfield et al 1987). This suggests that several variants of bovine GH exist in vivo, each which could differ with regard to physiology.…”
Section: Production Performance Of Dairy Cows Treated With Growth mentioning
confidence: 99%
“…The mechanism for this nutrition-dependant stimulation is currently unknown. As GH promotes lipolysis (Hart et al 1984, Dietz & Schwartz 1991, Richelsen 1997, perhaps the increased GH is meant to mobilize the excess fat represented by high leptin concentrations. Also of interest is the possibility that the increase in GH in leptin-treated diet-restricted lambs is a response associated with compensatory or 'catch-up' growth (Boersma & Wit 1997).…”
Section: Figurementioning
confidence: 99%
“…No início da década de 80, por intermédio da técnica do DNA recombinante, a somatotropina bovina começou a ser obtida em laboratório a partir de cultura de E. coli, conseguindo-se um produto sinté-tico de ação biológica idêntica à da proteína original, isenta de contaminantes e resíduos naturais (HART et al, 1984). O hormônio de crescimento ou somatotropina (GH ou ST) é uma proteína altamente complexa, constituída de 191 aminoácidos (WALLIS, 1973; GRAFF e LI, 1974), sendo naturalmente secretada pela glândula adenohipófise dos animais superiores.…”
Section: Introductionunclassified